Abdominal Wall Reconstruction with Mesh and Components Separation - Heller, Lior (Thieme Medical Publishers, 2012)
Incisional hernias in the abdominal wall are a by-product of multiple previous laparotomies. Unfortunately, the incidence of incisional hernias has risen, as we have progressed with new surgical techniques in the treatment of abdominal pathologies. Many methods have been attempted in the past to achieve a better and more durable repair, namely using components separation to bring the fascia into the midline, and reinforce incisional hernias with different mesh materials. The authors review the recent literature regarding the efficacy of these synthetic materials and biomaterials in incisional hernia repair, as well as share their experience in treating complex abdominal wall defects using components separation and biologic mesh.